The effectiveness of the median nerve neurodynamic mobilisation techniques in women with mild or moderate bilateral carpal tunnel syndrome: A single-blind clinical randomised trial - Hassan Beddaa; Bouchra Kably; Basma Marzouk; Ikrame Mouhi; Abdelghafour Marfak; Youness Azemmour; Ismail Bouzekraoui Alaoui; Nazha Birouk (AOSIS, 2022)
Background: Carpal tunnel syndrome (CTS) is the most prevalent upper limb compression neuropathy. Surgical or nonsurgical treatment is recommended. Both mild and moderate CTS can be managed conservatively. Neurodynamic mobilisation techniques (NMTs) of the median nerve have not been widely studied, and conflicting findings exist. Methods/design: Sixty-two female patients with mild or moderate bilateral CTS were assigned one wrist to the treatment group (TG) and the other to the control group (CG). Both groups underwent carpal bone mobilisation. The TG underwent NMTs while the CG received a placebo elbow mobilisation not targeting the median nerve. The Numerical Rating Pain Scale, JAMAR Plus Digital Hand dynamometer and Functional Status Scale (FSS) were used to assess pain, grip strength and functional status. Discussion: Comparison of groups showed that NMTs at 5 weeks decreased pain intensity by 1.15 (p = 0.001) and by 2 (p ˂ 0.001) at 10 weeks. Difference in functional status was 0.45 at 5 weeks (p = 0.003) and 0.84 at 10 weeks (p = 0.003). The CG's grip strength improved by 0.59 (p = 0.05) after 5 weeks and 0.61 (p = 0.028) at 10 weeks. Both groups improved in all parameters over time. Conclusion: When combined with carpal bone mobilisation, both NMTs and placebo elbow mobilisation seem to reduce pain intensity and improve grip strength and functional status. However, NMTs had better results in pain intensity and FSS. Clinical implications: Women with mild or moderate bilateral CTS may benefit from NMTs as a conservative treatment option. Trial registration: Pan African Clinical Trials Registry, PACTR202201807752672, https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=19340.